Antilisterial Activity of Ethanolic and Aqueous Extracts of the Leaves and Seeds of Moringa Oleifera - O.C, Eruteya; B, Badon (The Asia Journal of Applied Microbiology, 2014)
The in vitro antilisterial activity of the ethanolic and aqueous extracts of the leaves and seeds of Moringa oleifera were evaluated using the agar diffusion method on Mueller Hinton agar. Listeria monocytogenes PCM 2191 serovar 01/2 and the four other L. monocytogenes strains were inhibited by the aqueous extracts at the concentrations of 200 and 250mg/ml of the leaves and 150, 200 and 250mg/ml of the seeds whereas, no inhibitory effects were observed with the ethanolic extracts of both the leaves and seeds. The result of this study has demonstrated the potential application of moringa aqueous extract in the control of L. monocytogenes.